Strategi Pemberdayaan Kelompok Wanita Tani Sanur Asri Lestari dalam Pengembangan Urban Farming di Desa Sanur Kauh, Kecamatan Denpasar Selatan - UTARI, NI KADEK SRI; PUTRA, I GEDE SETIAWAN ADI; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.3, Desember 2020, 2020)
Strategy For Empowerment Of Women’s Farmer Group  Sanur Asri Lestari In The Development Of Urban Farming In Sanur Kauh Village, Kecamatan Denpasar Selatan Sanur Asri Lestari Women Farmers Group (hereafter KWT) is a women farmers organization consisting of 34 members in the village of Sanur Kauh. It is designated asKawasan Rumah Pangan Lestari (KRPL), a project that aims to increase ??green areas, realize food security, and increase family income through the utilization of vacant land and owned yard. The purpose of this research is to develop strategies and efforts to empower KWT. Research methods include (1) interviews with respondents and key informants (2) IFAS and EFAS matrix analysis, (3) formulation of alternative strategies with SWOT. The strategy that needs to be implemented is a growth strategy by introducing technological innovations such as drip irrigation. With IFAS matrix value of 3.10 and EFAS matrix value of 3.0, the IE matrix is ??in cell I (3.0 - 4.0). The result of empowering KWT proves that human development and business development are in good categories, institutional / organizational development in  medium category, and environmental development in  very good category. The KWT management organize activities that support group development such as hydroponic workshops to develop more diverse products while simultaneously managing the KWT garden gladually. The KWT members made direction board to go to  KWT garden, they alsocreating attractive logos and packaging designs. The government or related institutions provide training and assistance to KWT.